Structurally distinct telomere-binding proteins in Ustilago maydis execute non-overlapping functions in telomere replication, recombination, and protection - Yu, Eun Young (Commun Biol, 2020)
Duplex telomere binding proteins exhibit considerable structural and functional diversity in fungi. Herein we interrogate the activities and functions of two Myb-containing, duplex telomere repeat-binding factors in Ustilago maydis, a basidiomycete that is evolutionarily distant from the standard fungi. These two telomere-binding proteins, UmTay1 and UmTrf2, despite having distinct domain structures, exhibit comparable affinities and sequence specificity for the canonical telomere repeats. UmTay1 specializes in promoting telomere replication and an ALT-like pathway, most likely by modulating the helicase activity of Blm. UmTrf2, in contrast, is critical for telomere protection; transcriptional repression of Umtrf2 leads to severe growth defects and profound telomere aberrations. Comparative analysis of UmTay1 homologs in different phyla reveals broad functional diversity for this protein family and provides a case study for how DNA-binding proteins can acquire and lose functions at various chromosomal locations. Our findings also point to stimulatory effect of telomere protein on ALT in Ustilago maydis that may be conserved in other systems.